STUDI ADAPTASI BANJIR DI PERMUKIMAN TEPIAN SUNGAI DI KAWASAN TELUK GONG - Gilbert, Thomas; Herlambang, Suryono; Wipranata, B. Irwan (Jurusan Arsitektur dan Perencanaan, 2024)
Floods are disasters caused by nature or man-made, floods caused by nature such as continuous high-intensity rain, overflowing river water so that it enters the area and water sent from higher locations while floods caused by man-made such as canals blocked water is caused by careless dumping of rubbish, residential construction on riverbanks and the lack of water catchment areas caused by land use conversion. However, floods in the city of Jakarta contain natural and artificial elements, where the artificial elements are due to population growth which continues to increase so that residential development also increases which causes limited space, resulting in the conversion of land use for residential construction, this causes the area's inability to absorb water. The location of the area is in Kelurahan Pejagalan which is between Kali Angke and Kanal Banjir Barat, especially on the banks of the Kali Angke which are full of buildings and residential construction on embankments which causes damage to the embankments which is one of the potential causes of flooding in the area, while the banks of KBB are different from the edge of the Kali Angke which is without any buildings. So, the study of the Teluk Gong area, which is located between the Kali Angke and Kali KBB, aims to determine water runoff in the area using rational method and the causes of flooding in the area. The writing method is used using a qualitative approach with a description of the descriptive method with data collection techniques through surveys, literature studies, journals, books, and information from the internet. Keywords: flood; riverfront; water runoff; settlement Abstrak Banjir merupakan bencana yang disebabkan oleh alam maupun buatan manusia, banjir yang disebabkan oleh alam seperti hujan dengan intensitas tinggi tanpa henti, meluapnya air sungai sehingga masuk ke dalam kawasan dan air kiriman yang berasal dari lokasi yang lebih tinggi sedangkan banjir yang disebabkan buatan manusia seperti saluran air yang tersumbat disebabkan pembuangan sampah sembarangan, pembangunan hunian di tepi sungai dan minimnya daerah resapan air yang disebabkan pengalihfungsian dari penggunaan lahan. Namun banjir pada Kota Jakarta terdapat unsur alam dan buatan yang di mana unsur buatan dikarenakan pertambahan penduduk yang terus bertambah sehingga pembangunan hunian ikut bertambah yang menyebabkan keterbatasan tempat sehingga adanya pengalihfungsian dari penggunaan lahan untuk pembangunan hunian, Hal tersebut menyebabkan ketidakmampuan kawasan dalam menyerap air. Lokasi kawasan terletak di Kelurahan Pejagalan yang berada di antara Kali Angke dan Kanal Banjir Barat, khususnya pada tepian Kali Angke yang penuh dengan bangunan serta pembangunan hunian di atas tanggul yang menyebabkan kerusakan tanggul yang merupakan salah satu potensi penyebab banjir pada kawasan sedangkan tepi Kali KBB berbeda dengan tepi Kali Angke yang kondisinya tanpa ada bangunan. Maka studi kawasan Teluk Gong yang terletak di antara Kali Angke dan KBB bertujuan untuk mengetahui limpasan air pada kawasan dengan metode rasional dan penyebab dari banjir di Kawasan. Metode penulisan digunakan menggunakan pendekatan kualitatif dengan penjabaran metode deskriptif dengan teknik pengumpulan data melalui survei, studi literatur, jurnal, buku dan informasi berasal dari internet.